The application and prospects of antimicrobial peptides in antiviral therapy - Fei Yang; Yunqi Ma (Amino Acids)
Abstract Antimicrobial peptides (AMPs) have broad-spectrum antimicrobial activity, enabling them to rapidly detect and eliminate targets. In addition, many AMPs are natural peptides, making them promising candidates for therapeutic drugs. This review discusses the basic properties and mechanisms of action of AMPs, highlighting their ability to disrupt microbial membranes and modulate host immune responses. It also reviews the current state of research into using AMPs against various viral infections, focusing on their therapeutic potential against viruses that contribute to the global health crisis. Despite promising developments, therapies based on AMPs still face challenges such as stability, toxicity, and production costs. In this text, we will discuss these challenges and the latest technological advances aimed at overcoming them. The combination of nanotechnology and bioengineering approaches offers new ways to enhance the delivery, efficacy, and safety of AMPs. We emphasize the importance of further research to fully exploit the potential of AMPs in antiviral therapy, advocating a multifaceted approach that includes optimizing clinical use and exploring synergies with existing antiviral drugs.